THE EFFECT OF TAX DIGITALIZATION ON TAXPAYER COMPLIANCE (CASE STUDY ON SELLERS IN E-COMMERCE) - Shirley Martini; Yati Mulyati (Jurnal Ekonomi, 2023)
At present, the development of information technology has helped and supported various fields of government. One of its uses is in the field of taxation, namely tax digitalization. The presence of tax digitalization as a form of modernization of tax administration makes it easier for the community, especially taxpayers, to carry out their obligations. The involvement of technology in this innovation is expected to increase taxpayer compliance in carrying out their obligations, namely self-registration, tax deposits, and submission of tax returns through a electronic system in the form of e-Registration, e-Billing, with e-Filing. The presence of this system provides practicality to all taxpayers, including taxpayers as business actors who use e-commerce platforms in selling and marketing the products or services sold. This study aims to determine the effect of tax digitalization, namely e-Registration, e-Billing, and e-Filing on business taxpayer compliance, namely sellers in e-commerce. The type of research data used is primary data obtained from answers to questionnaires that have been distributed to sellers on e-commerce platforms. The Likert scale is used in this study as a scale measurement. The data analysis method used is multiple linear regression. The results showed that the implementation of e-Registration and e-Billing had a positive and significant effect on taxpayer compliance while e-Filing did not affect taxpayer compliance. The magnitude of the influence of e-Registration, e-Billing, and e-Filing contributed 51.2% to taxpayer compliance.